Alternate arm modular multilevel converter energy balancing via overlap onset control. Issue 16 (5th February 2019) - Howell, Steven; Wang, Haiyue; Filizadeh, Shaahin
Abstract : This study introduces a novel method called overlap onset control (OOC) to balance and maintain alternate arm modular multilevel converter (AAC) submodule capacitor voltages at their desired value. OOC performs zero‐current switching and controls the timing of AAC commutation to regulate submodule voltages while retaining output voltage quality. The study uses steady‐state converter models to develop the mathematical foundations behind the proposed capacitor voltage regulation method and then presents electromagnetic transient simulation results in PSCAD/EMTDCto demonstrate OOC's ability to extend the AAC operating range.